UPAYA MENUJU CITA-CITA KHIL?FAH ISL?MIYYAH:: Posisi Ikhw?n al-Muslim?n di Tengah Kemelut Mesir - Bahrul Ulum (MAQASHID Jurnal Hukum Islam, 2019)
Ikhw?n al-Muslim?n is one of the largest da'wah congregations that continues to carry out its various activities. The sympathizers, supporters and cadres are scattered in various regions throughout the world. They carried out their da'wah activities by referring to the various directions and thoughts that were spawned by the great thinker of Ikhw?n al-Muslim?n as well as its founder, Im?m Syah?d Hasan al-Bann?. Initially, Ikhw?n al-Muslim?n movement engaged in social and educational fields. Some of the activities include the establishment of polyclinics, mosques, schools, factories, eradication of illiteracy, publication of religious books, and daily and magazine publications. Over time, its movement began to enter into the problem of political realm. The journey of Ikhw?n al-Muslim?n is full of tribulations. Obstacles and challenges, especially from the Egyptian Government, are an integral part of the history of Ikhw?n al-Muslim?n, since the first quarter of the 20th century up to the present time with the dynamics of ups and downs and full of tragedy in realizing their ideals namely the establishment of the Islamic Caliphate.